Characterization of Chitosan Edible Film by Addition of Salt Solution as an Antibacterial - Zhanifathul Abhidah, Noer Rahmah; Sulmartiwi, Laksmi; Amin Alamsjah, Mochammad (Universitas Airlangga, 2025)
Edible film is a type of bioplastic in the form of a thin layer that can be consumed along with food products. It functions as a barrier to O₂ and CO₂ and helps control dissolved substances by reducing moisture, respiration, and oxidation rates without altering food components. To enhance its functionality, edible film can be fortified with active substances such as natural antimicrobials—one of which is salt, known for its ability to inhibit bacterial growth. This research is important in the development of bioplastics as it offers an environmentally friendly solution for food packaging, reducing reliance on conventional plastics and chemical preservatives. The study aims to analyze the effect of adding salt solution (0%, 2%, 4%, and 6%) on the microbiological and physical characteristics of chitosan-based edible film. Physical data were analyzed using a one-factor Completely Randomized Design (CRD), followed by ANOVA and Duncan’s Multiple Range (DMRT) tests. The results showed that chitosan edible film could inhibit Staphylococcus aureus with an inhibition zone diameter of 4.88 mm, categorized as weak antibacterial activity. The physical characteristics of the film showed significant variations, with thickness ranging from 0.062–0.074 mm, tensile strength from 1.127–1.822 MPa, and elongation from 115.7–120.3%. Overall, chitosan edible film with added salt solution met the Japanese International Standard JIS Z-1707, indicating its potential as a safer and more environmentally friendly food packaging material.Keywords: Antibacterial, edible film, salt, chitosan, quality